How does Law No. 6/2014 on Villages Reshape the Role and Function of Padukuhan? Case Study in Bantul Regency, Indonesia - Minardi, Minardi; Triwidaryanta, Jaka (Jurnal Studi Ilmu Pemerintahan, 2024)
This research examines the effects of Law No. 6 of 2014 on Villages on the role and positioning of Padukuhan within the village framework, focusing on Pulokadang and Canden Sub-Villages in Kapanewon Jetis, Bantul Regency, Yogyakarta Special Region Province. Through in-depth interviews with expert informants and document analysis, the study reveals several key findings. Firstly, it uncovers a lack of formal education or training for Padukuhan heads in local customs and culture, highlighting a need for cultural development initiatives in Bantul Regency. Furthermore, it identifies a limited scope of Padukuhan activities, primarily centered on management without adequate promotion of village potentials or addressing community issues. The study also notes community-driven efforts in constructing and operating Padukuhan facilities, supplemented by occasional political support through aspiration funds exchange for votes. These findings underscore the importance of enhancing Padukuhan functions within the village context post the enactment of Law No. 6 of 2014. By addressing gaps in cultural education, expanding the scope of Padukuhan activities to encompass community development, and establishing transparent mechanisms for political engagement, this research offers insights into optimizing the role of Padukuhan in local governance and community empowerment. This study contributes to the discourse on village governance and development in Indonesia, offering practical implications for policymakers and stakeholders seeking to leverage the potential of Padukuhan within the framework of Law No. 6 of 2014.